Trust, Transparency, and Replication in Political Science. Issue 1 (3rd January 2017) - Laitin, David D.; Reich, Rob
ABSTRACT: Striving better to uncover causal effects, political science is amid a revolution in micro-empirical research designs and experimental methods. This methodological development—although quite promising in delivering new findings and discovering the mechanisms that underlie previously known associations—raises new and unnerving ethical issues that have yet to be confronted by our profession. We believe that addressing these issues proactively by generating strong, internal norms of disciplinary regulation is preferable to reactive measures, which often come in the wake of public exposés and can lead to externally imposed regulations or centrally imposed internal policing.